Kebijakan Formulasi Tindak Pidana Informasi dan Transaksi Elektronik Dalam Pembaharuan Hukum Pidana Indonesia - I Gusti Agung Kiddy Krsna Zulkarnain; Eko Soponyono (Criminal of Law Department, Faculty of Law, Pattimura University, 2021)
The Electronic Information and Transactions Law brings several new legal concepts that are intended to resolve a polemic for the parties involved, however, the existing regulations do not appear to have reduced the crime but experienced an increase and also in In this Law, a juridical problem still arises which can be said to be quite fatal. This study aims to examine current and future information and electronic transaction formulation policies related to the current and future. This research uses normative legal research methods. The results are the policy of formulation of criminal information and electronic transactions in the present there are still some juridical problems that arise and it is hoped that in the future a revision will be made in this law.